A rapid technique for extraction of urinary 17-kéto and 17-hydroxy-corticosteroids by chromatography (author's transl) - Reboul-Salze, S; Enjolras, F; Gentou, C (Pathologie biologie (Paris), 1981)
The extraction ot total urinary 17-keto and 17-hydroxy steroids has been effected by a rapid procedure involving pre-packed kieselguhr column chromatography. This work successively studies the correlation of this technique with the classical extraction by mechanical agitation (42 and 61 subjects), its reproducibility, repeatability and recovery of added internal standards. The proposed method seems convenient for routine clinical analysis.